1996
DOI: 10.1002/pro.5560050718
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound states of α‐lactalbumin: Implications for the protein stability and conformation

Abstract: Abstracta-Lactalbumin (a-LA) associates with dimyristoylphosphatidylcholine (DMPC) or egg lecithin (EPC) liposomes. Thermal denaturation of isolated DMPC or EPC a-LA complexes was dependent on the metal bound state of the protein. The intrinsic fluorescence of thermally denatured DMPC-a-LA was sensitive to two thermal transitions: the T,. of the lipid vesicles, and the denaturation of the protein. Quenching experiments suggested that tryptophan accessibility increased upon protein-DMPC association, in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 79 publications
3
44
1
Order By: Relevance
“…The intrinsic fluorescence emission red shift and general increase resembles studies in which apo-␣-LA was transferred from aqueous media and embedded in the surface of liposomes (11,12). Although there are several mechanisms to explain the fluorescence changes, one model could even be consistent with identical binding sites for both stearic acid and 5-DSA.…”
Section: Discussionmentioning
confidence: 60%
“…The intrinsic fluorescence emission red shift and general increase resembles studies in which apo-␣-LA was transferred from aqueous media and embedded in the surface of liposomes (11,12). Although there are several mechanisms to explain the fluorescence changes, one model could even be consistent with identical binding sites for both stearic acid and 5-DSA.…”
Section: Discussionmentioning
confidence: 60%
“…Hen egg white LYS and bovine LA are homologous to each other as they share similar primary structures, but their unfolding profiles and the stabilities of their native conformations are very different (Cawthern, Permyakov, & Berliner, 1996;Polverino de Laureto et al, 2002). The biological functions of LYS, such as its antimicrobial and immunomodulating properties, have been attributed to its ability to interact with membrane component phospholipids and to penetrate into lipid bilayers, aspects which have been broadly studied (Gorbenko, Loffe, & Kinnunen, 2007;Yuan et al, 2007).…”
Section: Effect Of the Presence Of Pc On The Gastric Digestion Of Lysmentioning
confidence: 99%
“…These authors concluded that specific hydrophobic interactions with the sn-2 acyl chain are a major determinant for the binding of annexin V to membranes (35). Finally, the lipid binding properties of milk protein ␣-lactalbumin closely resemble those of cyt c (36). Moreover, lipid binding to ␣-lactalbumin has been suggested to induce the molten globule state, similarly to cyt c (37,38).…”
Section: Lipid-induced Changes In the Absorption Spectra Of Cyt C-inmentioning
confidence: 99%